A Relative Paleointensity (RPI)-Calibrated Age Model for the Corinth Syn-rift Sequence at IODP Hole M0079A (Gulf of Corinth, Greece) - Maffione, Marco; Herrero-Bervera, Emilio (Frontiers in Earth Science, 2022)
The Corinth basin (Greece) is a young continental rift that recorded cyclic basin paleoenvironment variations (i.e., marine to lacustrine) caused by glacio-eustatic sea level fluctuations during its initial connection to the global oceans. The Corinth syn-rift sequence offers therefore a unique opportunity to determine the timing and modality of connection of young rifts to the global oceans, and investigate how sediment supply change during this extremely dynamic stage of their evolution. Here we use magnetostratigraphic and relative paleointensity (RPI) constraints from 885 discrete samples from International Ocean Discovery Program (IODP) Hole M0079A to generate an unprecedented high-resolution (∼15kyr) age model for the youngest part of the Corinth’s offshore syn-rift sequence. Our RPI-calibrated age model spans the last ∼850 kyr and reveals that initial connection of the Corinth basin to the Mediterranean Sea occurred at ∼530 ky, more recently than previously thought and after a short-lived marine incursion at ∼740 kyr. Accumulation rates calculated from our age model indicate two significant changes in sediment supply at 530 (from 74 to 156 cm/kyr on average) and 70 ka (from 156 to 258 cm/kyr on average), interpreted as due to increased local fault activity in the southern margin of the Corinth basin. Sedimentation rates also display a short-term variation indicating a lower sediment supply (98 cm/kyr on average) during interglacial periods and a higher input (156 cm/kyr on average) during glacial periods. We conclude that long-term variations of sediment supply in young rifts connecting to the global oceans are predominantly controlled by local tectonics (i.e., new depocenters formation), while short-term variations may be driven by global climate (i.e., increased erosion aided by fewer vegetation during glacial periods). Grain size of the Corinth syn-rift sequence shows a weak correlation with glacial cycles too (i.e., coarser sediments during interglacials), but we suggest this to be controlled by the hydrodynamics of the basin (i.e., stronger bottom currents when the basin was connected to the Mediterranean Sea during interglacial periods).